Effect of nicotine exposure during pregnancy on birth weight among beedi rolling women - M. N., Astagimath; A., Veena (International Journal of Research in Medical Sciences, 2019)
Background: Exposure to nicotine can lead to increased morbidity and mortality among fetus and mothers. The objective was to study the effect of nicotine exposure on the birth weight of the babies. Methods: During the study period of one year, it was possible to recruit the total 144 subjects. 36 were women who were exposed to nicotine as they were bidi rollers. The exposure was confirmed by history. 36 women delivered during the study period and these newborns were included in the present study. Control group were 36 pregnant women who were not exposed to nicotine. They were asked about the exposure history, like anyone in their family is smoking inside the house any time and their occupation. Among these all (36) delivered during the study period and their newborns were included in the present study. Results: Both the groups were comparable in terms of age, hemoglobin, body mass index, gestational age. The mean birth weight of babies in the control group (whose mothers were not exposed) was 3.01kg with a standard deviation of 0.56 compared to mean birth weight of babies in the study group (whose mothers were not exposed) of 2.73kg with a standard deviation of 0.40. This difference in the mean birth weight of babies in the study group and the control group was found to be statistically significant (p<0.05). The mean serum cotinine value in study group mothers and babies was very high compared to zero value in mothers and babies of control group and statistically significant (p<0.05). Conclusions: Maternal nicotine exposure through beedi rolling is associated with reduced birth weight.